Regenzeiten, Feuchtgebiete, Körpersäfte: Das Wasser in der klassischen indischen Medizin - Angermeier, Vitus (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
This monograph analyses the role of water in classical Indian medicine on the basis of its source texts. In three large sections, Angermeier discusses the medical relevance of nature and climate, the role of water in the human body and its dietary and medical use. Within these three categories, topics as diverse as hydrology, seasonology, anatomy and physiology, the elemental doctrines as well as therapeutic practice are dealt with offering multi-layered insights into the intellectual history of early Ayurveda.